CAR-T treatment for cancer: prospects and challenges - Chen, Ran; Chen, Lei; Wang, Chaoqun; Zhu, Hua; Gu, Lijuan; Li, Yuntao; Xiong, Xiaoxing; Chen, Gang; Jian, Zhihong (Frontiers in Oncology, 2023)
Chimeric antigen receptor (CAR-T) cell therapy has been widely used in hematological malignancies and has achieved remarkable results, but its long-term efficacy in solid tumors is greatly limited by factors such as the tumor microenvironment (TME). In this paper, we discuss the latest research and future views on CAR-T cell cancer immunotherapy, compare the different characteristics of traditional immunotherapy and CAR-T cell therapy, introduce the latest progress in CAR-T cell immunotherapy, and analyze the obstacles that hinder the efficacy of CAR-T cell therapy, including immunosuppressive factors, metabolic energy deficiency, and physical barriers. We then further discuss the latest therapeutic strategies to overcome these barriers, as well as management decisions regarding the possible safety issues of CAR-T cell therapy, to facilitate solutions to the limited use of CAR-T immunotherapy.